2020
DOI: 10.1111/1467-6427.12309
|View full text |Cite
|
Sign up to set email alerts
|

Alliance discrepancies in home‐based family treatment: occurrence, development and the therapist’s perspective

Abstract: Alliance discrepancies in home-based family treatment: occurrence, development and the therapist's perspective M.J. Welmers-van de Poll , a,b G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Second, like Welmers-van de Poll et al (2020), we examined the alliance from all three perspectives. However, unlike that study and many other FT studies that used an alliance measure originally developed for individual psychotherapy, we used the SOFTA-s (Friedlander et al, 2006), which asks therapists to report on their alliance with the family unit and clients to report on their personal experience of the alliance and the perceived experiences of other family members, including within-family collaboration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, like Welmers-van de Poll et al (2020), we examined the alliance from all three perspectives. However, unlike that study and many other FT studies that used an alliance measure originally developed for individual psychotherapy, we used the SOFTA-s (Friedlander et al, 2006), which asks therapists to report on their alliance with the family unit and clients to report on their personal experience of the alliance and the perceived experiences of other family members, including within-family collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Over several decades, an increasing number of naturalistic studies conducted in community agencies (e.g., Escudero et al, 2008;Friedlander et al, 2008) and families' homes (e.g., Bachler et al, 2016;Johnson et al, 2002;Welmers-van de Poll et al, 2020) provided valuable information about how meaningful change can take place in family therapy (FT; Heatherington et al, 2015). To contribute to knowledge in this area, we conducted a processoutcome study with maltreated youth and their caregivers focusing on the therapeutic alliance, which has repeatedly been associated with outcome in couple and FT, meta-analytic r = .248, p < .001 (Friedlander et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these differences, the alliance is integral to successful psychotherapy with young people and their families (Karver et al, 2018(Karver et al, , 2019McLeod, 2011;Roest et al, 2023a). However, it is argued that the alliance should be measured from a dyadic or even systemic perspective, especially in family treatment (Roest et al, 2023b;Welmers-Van de Poll et al, 2020).…”
mentioning
confidence: 99%
“…Despite the importance of comparing the therapist's view of the alliance to those of youth and caregivers, we located one family therapy study that did so (Welmers‐van de Poll et al, 2020). Results showed that therapists’ perceptions of the alliance were less congruent with the perceptions of adolescents than with those of their parents, particularly the mothers.…”
mentioning
confidence: 99%